Analysis Influence of Human Resource Management Practices on Study Employee Performance at PO. Haryanto Kudus - Novita Yuliana; Fuad Mas'ud (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2020)
Islamic business management has begun to applied by several companies to set and achieve goals. The phenomenon shows that there are companies that implement Islamic business management that can achieve success, growing rapidly, and compete with others companies that do not apply Islamic business management principles. The company is PO. Haryanto Kudus. The success of a business is supported by several factors, one important factor is the support of human resources. A company needs to pay attention to human resource management to achieve the goals. This study aims to analyze the effect of human resource management practices on employee performance on PO. Haryanto Kudus. Data collection method are done through interviews and questionnaires. The object of this research are 83 employees at PO. Haryanto Kudus. This study uses multiple linear regression analysis techniques from the application of SPSS 23. The results of the analysis shows that employee recruitment and selection, performance appraisal, and compensation are in a positive and significant effect on employee performance in PO. Haryanto Kudus.Keywords: Human Resources, Recruitment and Selection of Employee, Performance Appraisal, Compensation.